Drugs Prescribed for Asthma and Their Adverse Effects on Dental Health - Edisson-Mauricio P; Jessica Jaramillo; Jéssica Sarmiento-Ordoñez; Katherine Cuenca-León (MDPI AG, 2023)
Asthma is a chronic, heterogeneous respiratory pathology characterized by reversible airway inflammation. Therapeutics focus on symptom reduction and control, aimed at preserving normal pulmonary function and inducing bronchodilatation. The objective of this review is to describe the adverse effects produced by anti-asthmatic drugs on dental health, according to the reported scientific evidence. A bibliographic review was carried out on databases, such as Web of science, Scopus, and ScienceDirect. Most anti-asthmatic medications are administered using inhalers or nebulizers, making it impossible to avoid contact of the drug with hard dental tissues and oral mucosa, and thus promoting a greater risk of oral alterations, mainly due to decreases in the salivary flow and pH. Such changes can cause diseases, such as dental caries, dental erosion, tooth loss, periodontal disease, bone resorption, as well as fungal infections, such as oral candidiasis.